Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
49
Step-by-step explanation:
Let the three numbers be a1, a2, a3
Let the number to be added to form a geometric progression = x
a1 = 1 + x ; a2 = 11 + x ; a3 = 23 + x
For a geometric progression :
a2 = a1 * r
a2 = (1+x)r
11+x = (1+x)r - - (1)
r = (11+x) / (1+x) ---(1)
a3 = a2 * r
a3 = (11+x)r
23+x = (11+x)r - - -
r = (23+x) / (11+x) - - (2)
Equate (1) and (2)
(11+x) / (1+x) = (23+x) / (11+x)
(11+x) * (11+x) = (23+x) * (1+x)
121 + 22x + x² = 23 + 24x + x²
121 + 22x + x² - x² - 24x - 23 = 0
98 - 2x = 0
-2x = - 98
x = 98 / 2
x = 49
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.